POLITICAL PROCESSES AND FIGURES OF 1917S VIEWED BY BRITISH MILITARY ATTACHE ALFRED KNOX - Porshneva, O.S. (Vestnik Rossijskogo universiteta družby narodov. Seriâ Istoriâ Rossii (Print), 2017)
The author offers an interpretation of Alfred Knox’s memoirs “With the Russian Army. The Diary of a Military Attache. 1914-1917” in order to reconstruct the political processes of the 1917 Russian Revolution as they were viewed by a western witness. The article considers Knox’s interpretation of the Russian Revolution’s pre-conditions, evolution and the causes of Bolshevik’s seizing power. The author analyzes the way Knox characterizes the events, describes the actors of the Revolution and political culture of the Russian people. The author shows that the main topic of Knox’s memoirs was the Russian army conditions which he considers in connection with the analysis of the military potential of Russia as an ally and the problem of inter-allied cooperation. The author discusses Knox’s explanation and description of the Russian people’s temper, his interpretation of the wide-spread Russian auto-stereotypes and his “colonial discourses”. The article shows that in Knox’s opinion Russian people’s self-reflection demonstrated establishing of the political cult of people/“ordinary people” as a source of the highest legitimacy. This was one of the bases of Bolsheviks’ legitimacy concept and their rights for power declared on behalf of “ordinary people”. The author argues that Knox’s evaluation of Russia as an ally was the main “prism of his perception” of the 1917 Russian Revolution events and Russian people’s behavior at that time. The other factors which influenced Knox’s explanations of particular revolutionary processes and Russian people’s temper were values of the British conservative political culture and traditional stereotypes about Russia and Russians shared by Knox.